Cloud computing enabled big-data analytics in wireless ad-hoc networks - Das, Sanjoy 1979-; Rao, Ram Shringar 1973-; Dāśa, Indrānī; Jain, Vishal 1983-; Singh, Nanhay 1973- (CRC Press, 2022)
"This reference text covers intelligent computing through Internet of Things (IoT) and Big Data in Vehicular Environment in a single volume. The text covers important topics including topology-based routing protocols, heterogeneous wireless networks, security risks, software-defined vehicular Ad-hoc network, vehicular delay tolerant networks, and energy harvesting for WSNs using rectenna"--
Includes bibliographical references and index. - Online resource; title from PDF title page (EBSCO, viewed April 4, 2022)
Keywords: Ad hoc networks (Computer networks); Cloud computing; Big data; Réseaux ad hoc (Réseaux d'ordinateurs); Infonuagique; Données volumineuses